Freshwater ecosystem macrophytes and microphytes: development, environmental problems, usage as raw material. Review - Soloviy, Khrystyna; Malovanyy, Myroslav (Lviv Politechnic Publishing House, 2019)
Classification of macrophytes and microphytes in the system of hydrobionts is presented, individual characteristics of each macrophyte and microphyte type according to the given classification are presented, environmental problems concerning uncontrolled development of macrophytes and microphytes in water media are considered and several biotechnologies of application of their sustainable development are characterized.
Keywords: macrophytes; microphytes; uncontrolled development; biomass; biotechnologies